2021
DOI: 10.21577/0103-5053.20200228
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Human Protein Targets for Soybean Isoflavones

Abstract: Soy isoflavones have been reported as endocrine disruptors due to their ability to modulate the activity of estrogen receptors (ERs) in mammals; however, its ability to modulate other metabolic pathways is not entirely clear, which makes it necessary to identify new pharmacological targets that interact with these compounds present in soybean. In this work, a virtual screening was executed to identify potential targets of nine soy isoflavones, employing human proteins target from PharmMapper. The best 25 fit s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Estimator plot (Hammer et al, 2001;Maldonado-Rojas et al, 2021), it can be seen that most of the resulting poses were found around 2.0-2.5 Å (Figure 3). This the in vitro study (Okaniwa et al, 2021).…”
Section: Resultsmentioning
confidence: 94%
“…Estimator plot (Hammer et al, 2001;Maldonado-Rojas et al, 2021), it can be seen that most of the resulting poses were found around 2.0-2.5 Å (Figure 3). This the in vitro study (Okaniwa et al, 2021).…”
Section: Resultsmentioning
confidence: 94%